Modelling and simulation of a smartgrid architecture for a real distribution network in the UK. Issue 8 (17th July 2019) - Yi, Jialiang; Pages, Chloe; Allahham, Adib; Giaouris, Damian; Patsios, Charalampos
Abstract : As part of the inteGRIDy project, funded by the European Commission, an investigation is carried out on a real distribution network, where high penetrations of distributed generations (DGs) exist, in the UK. In this study, a model of this network is built. In this model, additional energy storage systems are located in the network close to DGs to represent future smartgrid architecture. This architecture is proposed to reduce the power import and export between this network and the grid. Four test cases are designed to explore the impacts of DG and the benefits of ESSs.